(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Autism spectrum disorder has precipitously mounted globally since the early 1990s. The Autism rise in amount has flashed fears of an autism epidemic. Autism spectrum disorder (ASD) is a complex developing condition. Although ASD can be an enduring disorder, early diagnosis and treatments can improve a person’s symptoms and daily functioning. Study shows that 1 in 54 children has been diagnosed with autism spectrum disorder (ASD); it is a spectrum form, which means that all persons with autism represent certain difficulties. Since there is no specific diagnostic test, experts are still hunting for accurately what causes autism. The core features must be present in early development, like obstacles in social communication and interactions and restricted interests or repetitive behaviors. Multi F factors influence autism spectrum disorder, like gut-brain health, Microbiome dysfunction in the gastrointestinal tract, autoimmune disease, etc. Many research study findings are that probiotics may help diminish the inflammatory condition and modulate the Gastrointestinal problem and behavioral abnormality in ASD. Exclusive breastfeeding has the lowest risk of autism spectrum disorder; it decreases the 76 % chances of ASD. A proper supplement like folic acid during the first-trimester act as protective against ASD. Material and method: Relevant articles and literature were retrieved from different journals and web pages to find out the Autism details and how it related to various factors. J Bangladesh Coll Phys Surg 2022; 40: 197-203